Managing the Ksa’a’hko network: First Nations land governance practices that contribute to community wellbeing - Brears, Jordan (2020)
Self-determination is an important element in achieving improved wellbeing for First Nations communities. The First Nations Land Management Act (FNLMA) allows First Nations communities to self-govern land management functions through the development of community land codes, which houses a community’s land policies. Good governance is an important factor in building effective institutions and contributing to improved wellbeing. However, there is little available evidence that identifies what aspects of land codes constitute good governance and how they contribute to the community as a whole. This study utilizes a Qualitative Comparative Analysis to identify governance practices within First Nations land codes that contribute to improved socio-economic and cultural outcomes. The end result culminates into sets of recommended policies that are applicable for specific First Nations communities at different points of time along their FNLMA journey.